PENGARUH PERBANDINGAN AIR KELAPA DAN SARI SIRSAK TERHADAP KUALITAS MINUMAN BERKARBONASI DENGAN PENAMBAHAN NaHCO3 - Marlina, Lusi; Wijayanto, Yulfan (Jurnal TEDC, 2024)
Carbonated drinks have a sparkle effect with a typical soda taste in the mouth and generally use artificial flavors. Rarely use natural flavors. A new innovation in the manufacture of carbonated drinks is using coconut water as raw material with the addition of soursop fruit juice which is a natural flavor. Making carbonated drinks from coconut water and soursop juice is done by using sodium bicarbonate (NaHCO3) as a producer of CO2 gas. This study aims to determine the effect of the ratio of coconut water to soursop extract and sodium bicarbonate concentration to produce carbonated drinks with good quality. This study used a completely randomized design (CRD) with 2 factors, namely the ratio of coconut water to soursop extract and the concentration of sodium bicarbonate. The results showed that the highest levels of vitamin C were in KS1N1 with a ratio of coconut water: soursop essence (50: 50) and 0.7% NaHCO3, with vitamin C levels (26.4 mg/100 g) which were still acceptable TKPI Ministry of Health 2019, value total acid (0.282%) according to SNI 3719:2014, and the pH value (4.33) according to SNI 3708:2015. The best organoleptic results were for KS4N1 with a ratio of coconut water: soursop extract (80: 20) and 0.7% NaHCO3 with an organoleptic value of taste 4.7 (like), aroma 3.3 (rather like) and color 4.3 (like) . The results showed that the ratio of coconut water and soursop extract affects the quality of carbonated drinks.